PCAF, SIRT1 and the regulation of substrate acetylation - Serrano, L (2021)
Levels of lysine acetylation (KAc) in cells are regulated by epigenetic enzymes with opposing roles; histone acetyl transferases (HATs) and histone deacetylases (HDACs). The HAT p300 CBP associating factor (PCAF) and the sirtuin HDAC SIRT1 have protein substrates in common, including histone 3 (H3) at lysine residues 9 and 14 (H3K9 and H3K14) and non histone protein hypoxia inducible factor 1α (HIF1α). Studying PCAF and SIRT1 in parallel helps understand how levels of acetylation are maintained by the two classes of proteins.